Association between anthropometric indices of obesity and risk of cardiovascular disease in Japanese men. Issue 1 (21st November 2019) - Xiang, Mi; Hu, Huanhuan; Imai, Teppei; Nishihara, Akiko; Sasaki, Naoko; Ogasawara, Takayuki; Hori, Ai; Nakagawa, Tohru; Yamamoto, Shuichiro; Honda, Toru; Okazaki, Hiroko; Uehara, Akihiko; et al.
Abstract: Objectives: We aimed to compare the association of body mass index (BMI), waist circumference (WC), and waist‐to‐height ratio (WHtR) with risk of cardiovascular disease (CVD) among middle‐aged working Japanese men. Methods: A nested case‐control study was performed among middle‐aged male employees who underwent periodic health checkup. A total of 241 CVD cases were identified and matched individually on age, gender, and worksite with 1205 controls. Data on BMI, WC, WHtR, smoking, hypertension, diabetes, and dyslipidemia collected at 4 years before the event/index date were retrieved. Associations between BMI, WC, WHtR, and CVD risk were assessed by using conditional logistic regression models. Results: The strength of the association of BMI, WC, and WHtR with CVD risk was similar. The smoking‐adjusted odds ratio (95% confidence interval) for CVD was 1.60 (1.38‐1.85), 1.53 (1.33‐1.78), and 1.56 (1.35‐1.81) for a 1 SD unit increase in BMI, WC, and WHtR respectively. After further adjustment for hypertension, diabetes, and dyslipidemia, these associations were attenuated but remained statistically significant. Conclusions: Measures of general (BMI) and abdominal (WC and WHtR) obesity were similarly associated with CVD in middle‐aged Japanese men.